SCALP CYSTS ARE NOT ALWAYS SEBACEOUS IN ORIGIN TWO CASES OF OCCULT RENAL CELL CARCINOMA PRESENTING WITH SCALP NODULES: Occult Renal Cell Carcinoma - Khan, Muhammad Najam; Vidya, Raghavan; Lee, Richard (Pakistan Armed Forces Medical Journal, 2008)
.